Banking Sector Diversity and Socioeconomic Structure: Criteria for Matching Pairs - Horst Gischer; Christian Ilchmann (Vierteljahrshefte zur Wirtschaftsforschung, 2018)
It has been an age-old debate whether the financial structure matters for the real economy's efficiency and therefore for real outcomes. We suppose that varying socioeconomic conditions require appropriately designed corresponding financial sectors. For providing evidence, we firstly determine the specific (quantitative) size and corporate alignments of banking sectors across Europe, based on a sophisticated cluster analysis. Secondly, we develop a coherent system of geographic, social and economic parameters to identify structural patterns within the real economy's sector. In a conclusive synthesis, we link both analytical parts and draw tentative conclusions for possible future policy implications in Europe. – – Ob die Ausgestaltung des Finanzsektors eines Landes Auswirkungen auf die Effizienz der jeweiligen Realwirtschaft und damit Einfluss auf den realen Output nimmt, ist eine in der Literatur breit diskutierte Fragestellung. Das vorliegende Papier nähert sich der beschriebenen Thematik aus zwei Richtungen: Auf der einen Seite wird eine empirische Klassifikation unterschiedlicher Bankensysteme mittels Clusteranalyse vorgenommen. Auf der anderen Seite erfolgt eine Kategorisierung verschiedener sozioökonomischer Systeme. Eine sich daran anschließende Synthese stellt beides zueinander in Beziehung. Anhand ausgewählter Kriterien werden Aussagen über Interdependenzen und Kongruenz von Bankensystemen und Realwirtschaft getroffen, woraus sich mögliche Implikationen für ordnungspolitische Entscheidungen in der EU ergeben.
Keywords: E00; E02; E60; 330; European integration; economic integration; banking system structure; socioeconomic structure; Banking Union; banking business models